2016
DOI: 10.13060/00380288.2016.52.3.261
|View full text |Cite
|
Sign up to set email alerts
|

Civic Participation and Gender Beliefs: An Analysis of 46 Countries

Abstract: Abstract:Gender equality has progressed a great deal in recent decades in response to modernisation, industrialisation, and the generally rising level of education. A transformation in gender beliefs has accompanied the progress on gender equality and beliefs about gender roles have mainly changed in countries in North America and Europe, while in Muslim and Asian countries they have remained the same. The analysis in this article focuses on civic participation and investigates its relation to equalitarian gen… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
2
0

Year Published

2019
2019
2020
2020

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 63 publications
0
2
0
Order By: Relevance
“…For instance, Van der Meer et al (2009) have shown that members of leisure, activist and interest organizations vary with regard to political attitudes as well as trust in political institutions. Voicu and Voicu (2016) found significant differences between associations with regard to gender equality values: Whereas members of religious and sport organizations were more conservative, members of charity organizations turned out to be more liberal. Burrmann et al (2020) document differences in social trust levels between members of inwardand outward-oriented associations.…”
Section: Discussionmentioning
confidence: 95%
“…For instance, Van der Meer et al (2009) have shown that members of leisure, activist and interest organizations vary with regard to political attitudes as well as trust in political institutions. Voicu and Voicu (2016) found significant differences between associations with regard to gender equality values: Whereas members of religious and sport organizations were more conservative, members of charity organizations turned out to be more liberal. Burrmann et al (2020) document differences in social trust levels between members of inwardand outward-oriented associations.…”
Section: Discussionmentioning
confidence: 95%
“…In the paints case, stress factors usually act on the polymer matrix causing its degradation / ageing. In general, polymer degradation is a complex process in which a thermooxidation reaction [1][2][3][4][5][6][7][8][9] plays a determining role, which in the painting layers case is initiated by solar radiation in the IR spectrum and especially UV [10][11][12] and accelerated by climatic conditions specific to the operating environment [11,[13][14][15].…”
mentioning
confidence: 99%